Hepatic venous occlusion during cardiopulmonary bypass in patients with heterotaxy syndrome: A safe but underutilized option. - Edwin, F.; Sereboe, L.; Gyan, B. (My University, 2013)
Direct intracardiac drainage of separate right and left hepatic veins remote from each other (independent hepatic veins) in heterotaxy patients complicates procedures requiring cardiopulmonary bypass (CPB). Temporary occlusion of such independent hepatic veins during CPB is an alternative to cannulation but is rarely used because of concerns about acute congestive hepatopathy. Consequently, temporary single hepatic venous occlusion has not been well described as a safe and simple alternative to hepatic venous cannulation during CPB. We report 2 patients with the polysplenia variant of heterotaxy in whom independent hepatic veins were safely occluded for 55 and 86 minutes, respectively, in the course of intracardiac repair. Temporary hepatic venous occlusion simplified the CPB technique and minimized clutter of the operative field. The intrahepatic hemodynamics during CPB using temporary hepatic venous occlusion is illustrated.
Keywords: EMTREE drug terms: alanine aminotransferase; aspartate aminotransferase; politef; EMTREE medical terms: accessory spleen; adult; alanine aminotransferase blood level; aorta valve regurgitation; article; ascending aorta; aspartate aminotransferase blood level; cardiopulmonary bypass; case report; child; computed tomographic angiography; convalescence; cor triatriatum; coronary sinus; dextrocardia; female; heart atrium septum defect; hemodynamics; heterotaxy syndrome; hospital discharge; human; liver vein obstruction; postoperative period; preschool child; priority journal; recurrent disease; reoperation; MeSH: Adult; Cardiac Surgical Procedures; Cardiopulmonary Bypass; Catheterization; Child, Preschool; Drainage; Female; Hemodynamics; Hepatic Veins; Heterotaxy Syndrome; Humans; Intraoperative Period